2008
DOI: 10.1371/journal.pone.0003262
|View full text |Cite
|
Sign up to set email alerts
|

Herpes-Virus Infection in Patients with Langerhans Cell Histiocytosis: A Case-Controlled Sero-Epidemiological Study, and In Situ Analysis

Abstract: BackgroundLangerhans cell histiocytosis (LCH) is a rare disease that affects mainly young children, and which features granulomas containing Langerhans-type dendritic cells. The role of several human herpesviruses (HHV) in the pathogenesis of LCH was suggested by numerous reports but remains debated. Epstein-barr virus (EBV, HHV-4), & Cytomegalovirus (CMV, HHV-5) can infect Langerhans cells, and EBV, CMV and HHV-6 have been proposed to be associated with LCH based on the detection of these viruses in clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
1
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 49 publications
6
31
1
6
Order By: Relevance
“…We failed to find any statistically significant differences between patients with LCH and the control group with regard to the presence of HHV-6 DNA. This is in concordance with previous negative results reported in the literature (17)(18)(19).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We failed to find any statistically significant differences between patients with LCH and the control group with regard to the presence of HHV-6 DNA. This is in concordance with previous negative results reported in the literature (17)(18)(19).…”
Section: Discussionsupporting
confidence: 94%
“…The positive result in six (12.5%) of the control samples could be attributed to coincidence. P = 0.11, which shows no significant difference in HHV-6 detection results between the LCH patients and the controls, does not support the hypothesis of a possible role for HHV-6 in the pathogenesis of LCH disease, which is in keeping with some other reports in the literature (17)(18)(19).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…This seems unlikely because, at least so far, no microbial genomes have been identified in pathologic LCs and no epidemiological studies have suggested an infectious or environmental cause. Herpesviruses had been associated anecdotally with LCH but a recent study showed that the prevalence of antibodies against these viruses, as well as their titers, were the same in LCH patients and age-matched controls (Jeziorski et al, 2008).…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%